Question

Let x(t) be the solution of the initial-value problem(a) Find the Laplace transform F(s) of the forcing f(t).(b) Find the Laplace transform X(s) of the solution x(t).x"+8x'+20x=f(t)x(0)=-3x'(0)

Laplace transform
ANSWERED
asked 2020-12-25

Let x(t) be the solution of the initial-value problem
(a) Find the Laplace transform F(s) of the forcing f(t).
(b) Find the Laplace transform X(s) of the solution x(t).
\(x"+8x'+20x=f(t)\)
\(x(0)=-3\)
\(x'(0)=5\)
\(\text{where the forcing } f(t) \text{ is given by }\)
\(f(t) = \begin{cases} t^2 & \quad \text{for } 0\leq t<2 ,\\ 4e^{2-t} & \quad \text{for } 2\leq t < \infty . \end{cases}\)

Answers (1)

2020-12-26
given differential equation is x
\(x"+8x'+20x=f(t)\)
\(x(0)=-3\)
\(x'(0)=5\)
\(\text{where the forcing } f(t) \text{ is given by }\)
\(f(t) = \begin{cases} t^2 & \quad \text{for } 0\leq t<2 ,\\ 4e^{2-t} & \quad \text{for } 2\leq t < \infty . \end{cases}\)</span>
\(\therefore \ x"+8x'+20x=t^2+4e^{2-t}\)
\(\text{we know that } L\left[x"\right]=s^2X(s)-sX(0)-x'(0)\)
\(L\left[x'\right]=sX(s)-x(0)\)
\(L\left[t^n\right]=\frac{n!}{s^{n+1}} , L\left\{e^{-at}\right\}=\frac{1}{s+a}\)
\(\text{Step 2}\)
\(\text{Taking Laplace tranform of equation}\)
\(L\left[x"\right]+8L\left[x'\right]+20L\left[x\right]=L\left[t^2\right]+4e^2L\left\{e^{-t}\right\}\)
\(s^2(X(s))-sX(0)-x'(0)+8\left[s(X(s))-x(0)\right]+20X(s)=\frac{2!}{s^{2+1}}+\frac{4e^{2}}{s+1}\)
\(\therefore s^2X(s)-s(-3)-5+8(sX(s)-5)+20X(s)=\frac{2}{s^{3}}+\frac{4e^{2}}{s+1}\)
\(\therefore (s^2+8s+20)X(s)+3s-5-40=\frac{2}{s^{3}}+\frac{4e^{2}}{s+1}\)
\(\therefore (s^2+8s+20)X(s)+3s-45=\frac{2}{s^{3}}+\frac{4e^{2}}{s+1}\)
\(\therefore X(s)\left[s^2+8s+20\right]=\frac{2}{s^{3}}+\frac{4e^{2}}{s+1}+45-3s\)
\(\therefore x(s)=\frac{1}{s^2+8s+20}\left\{(45-3s)+\frac{2}{s^{3}}+\frac{4e^{2}}{s+1}\right\}\)
0
 
Best answer

expert advice

Need a better answer?

Relevant Questions

asked 2021-02-19

Use Laplace transform to solve the following initial-value problem
\(y"+2y'+y=0\)
\(y(0)=1, y'(0)=1\)
a) \(\displaystyle{e}^{{-{t}}}+{t}{e}^{{-{t}}}\)
b) \(\displaystyle{e}^{t}+{2}{t}{e}^{t}\)
c) \(\displaystyle{e}^{{-{t}}}+{2}{t}{e}^{t}\)
d) \(\displaystyle{e}^{{-{t}}}+{2}{t}{e}^{{-{t}}}\)
e) \(\displaystyle{2}{e}^{{-{t}}}+{2}{t}{e}^{{-{t}}}\)
f) Non of the above

asked 2021-03-07

use the Laplace transform to solve the initial value problem.
\(y"-3y'+2y=\begin{cases}0&0\leq t<1\\1&1\leq t<2\\ -1&t\geq2\end{cases}\)
\(y(0)=-3\)
\(y'(0)=1\)

asked 2020-12-27

Let f(t) be a function on \(\displaystyle{\left[{0},\infty\right)}\). The Laplace transform of fis the function F defined by the integral \(\displaystyle{F}{\left({s}\right)}={\int_{{0}}^{\infty}}{e}^{{-{s}{t}}} f{{\left({t}\right)}}{\left.{d}{t}\right.}\) . Use this definition to determine the Laplace transform of the following function.
\(\displaystyle f{{\left({t}\right)}}={\left\lbrace\begin{matrix}{1}-{t}&{0}<{t}<{1}\\{0}&{1}<{t}\end{matrix}\right.}\)

asked 2021-01-30

Use Laplace transform to find the solution of the IVP
\(2y'+y=0 , y(0)=-3\)
a) \(f{{\left({t}\right)}}={3}{e}^{{-{2}{t}}}\)
b)\(f{{\left({t}\right)}}={3}{e}^{{\frac{t}{{2}}}}\)
c)\(f{{\left({t}\right)}}={6}{e}^{{{2}{t}}}\)
d) \(f{{\left({t}\right)}}={3}{e}^{{-\frac{t}{{2}}}}\)

asked 2020-11-22

Find the Laplace transform of the given function
\(\begin{cases}t & 0,4\leq t<\infty \\0 & 4\leq t<\infty \end{cases}\)
\(L\left\{f(t)\right\} - ?\)

asked 2021-01-13

The function
\(\begin{cases}t & 0\leq t<1\\ e^t & t\geq1 \end{cases}\)
has the following Laplace transform,
\(L(f(t))=\int_0^1te^{-st}dt+\int_1^\infty e^{-(s+1)t}dt\)
True or False

asked 2021-02-16

Solution of I.V.P for harmonic oscillator with driving force is given by Inverse Laplace transform
\(y"+\omega^{2}y=\sin \gamma t , y(0)=0,y'(0)=0\)
1) \(y(t)=L^{-1}\bigg(\frac{\gamma}{(s^{2}+\omega^{2})^{2}}\bigg)\)
2) \(y(t)=L^{-1}\bigg(\frac{\gamma}{s^{2}+\omega^{2}}\bigg)\)
3) \(y(t)=L^{-1}\bigg(\frac{\gamma}{(s^{2}+\gamma^{2})^{2}}\bigg)\)
4) \( y(t)=L^{-1}\bigg(\frac{\gamma}{(s^{2}+\gamma^{2})(s^{2}+\omega^{2})}\bigg)\)

asked 2020-12-25

\(L\left\{t-e^{-3t}\right\}\)
which of the laplace transform is
\(1.)\ L\left\{t-e^{-3t}\right\}=\frac{1}{s^{2}}+\frac{1}{s-3}\)
\(2.)\ L\left\{t-e^{-3t}\right\}=\frac{1}{s^{2}}-\frac{1}{s-3}\)
\(3.)\ L\left\{t-e^{-3t}\right\}=\frac{1}{s^{2}}+\frac{1}{s+3}\)
\(4.)\ L\left\{t-e^{-3t}\right\}=\frac{1}{s^{2}}-\frac{1}{s+3}\)

asked 2021-01-13

Find Y(t) using Laplace transform.
\(\displaystyle{y}{''}+{2}{y}'+{5}{y}={e}^{{-{T}}} \sin{{T}}\)
\(y(0)=0 , y'(0)=1\)

asked 2021-01-31

Compute the Inverse Laplace Transform of \(F(s) =\frac{s}{R^2s^2+16\pi^2}\)
take \(R=70\)

...